Organisational theory - Crowther, David; Green, Miriam (London : Chartered Institute of Personnel and Development, 2004)
The authors provide a theoretical framework to enable students to place organisational practice in a theoretical context. The text thus constitutes a solid knowledge base in organisational theory and in the application of that theory.
Includes bibliographical references and index.
Keywords: Organizational behavior; Society